Contents of plasma М2-pyruvate kinase (M2-РК) in patients with inflammatory bowel diseases - Ye. A. Konovich; I. L. Khalif (Российский журнал гастроэнтерологии, гепатологии, колопроктологии, 2010)
Aim of investigation. Assessment of М2-pyruvate kinase level (M2-РК) at patients with ulcerative colitis (UC) and Crohn’s disease (CD) and its relation to course, clinical and endoscopical activity of disease.Material and methods. Overall 70 patients were investigated: 42 – with UC, 15 – with CD, 13 – with irritable bowel syndrome (IBS) and 10 healthy patients. Blood plasma concentration of M2-РК was determined by solid-phase sandwich method of enzyme-linked immunoassay with application of «ScheBo» (Germany) test-systems.Results. The level of M2-РК in patients with UC, CD, IBS and healthy persons was 29,1±3,0, 17,3±1,5, 7,9±1,6 and 7,0±1,5 U/ml respectively (р<0,05 – for UC and CD in comparison to IBS and control group and for UC in comparison to CD). The level of M2-РК considerably raised in patients with severe (45,9±6,4 U/ml) and moderate (20,9±3,2 U/ml) UC, including steroid-resistant patients (61,5±6,2 U/ml), in comparison to patients in remission (11,0±1,8 U/ml, р><0,05) and at patients with chronic continuous course in comparison to chronic relapsing course (40,3±5,0 and 22,7±3,8 U/ml, р><0,05). The level of M2-РК had the strong tendency to increase with progression of endoscopic activity of UC. Increase of M2-РК concentration (М±σ of the control group, р><0,05) was observed in 76,2% of UC patients, at 73,3% of patients with CD and in 15,4% of patients with IBS.>< 0,05 – for UC and CD in comparison to IBS and control group and for UC in comparison to CD). The level of M2-РК considerably raised in patients with severe (45,9±6,4 U/ml) and moderate (20,9±3,2 U/ml) UC, including steroid-resistant patients (61,5±6,2 U/ml), in comparison to patients in remission (11,0±1,8 U/ml, р<0,05) and at patients with chronic continuous course in comparison to chronic relapsing course (40,3±5,0 and 22,7±3,8 U/ml, р><0,05). The level of M2-РК had the strong tendency to increase with progression of endoscopic activity of UC. Increase of M2-РК concentration (М±σ of the control group, р><0,05) was observed in 76,2% of UC patients, at 73,3% of patients with CD and in 15,4% of patients with IBS.>< 0,05) and at patients with chronic continuous course in comparison to chronic relapsing course (40,3±5,0 and 22,7±3,8 U/ml, р< 0,05). The level of M2-РК had the strong tendency to increase with progression of endoscopic activity of UC. Increase of M2-РК concentration (М±σ of the control group, р<0,05) was observed in 76,2% of UC patients, at 73,3% of patients with CD and in 15,4% of patients with IBS.>< 0,05) was observed in 76,2% of UC patients, at 73,3% of patients with CD and in 15,4% of patients with IBS.Conclusions. Blood level of M2-РК of patients with UC and CD increases considerably. Elevation of M2-РК level at patients with UC is associated to enhancement of clinical and endoscopical activity, chronic continuous course and steroid-resistance.